Fractal koch antenna for indoor tv and fm reception - Ong, Hui Niang (2013)
Many resources in the internet guide user to build an easy to construct and simple homemade TV and FM antenna. The antenna are just using some recycle materials and just two conductor such as copper wire as a dipole antenna. Since TV channel and FM is still in Very High Frequency (VHF) frequency band from 47MHz to 230MHz and Ultra High Frequency (UHF) frequency band from 470MHz to 798MHz, the maximum antenna height will be very long around 3 meters. Hence, half wavelength dipole antenna using Fractal Koch Curve technique was designed in order to miniaturize the antenna height with a given total surface area or volume. The standard dipole, Koch Curve Dipole Antenna with one iteration and 2 iteration was analysed and optimized at VHF and UHF using 3D simulator software Computer Simulation Technology (CST). Dipole with the Koch Curve iteration 1 and 2 has shown at least 11.87% and 16.1% reduction in size as compared to the standard dipole which have the same resonant frequency with a return loss magnitude less than -10dB.